The Role of Independent Curriculum in Developing Students' Creative and Innovative Skills in the Era of Society 5.0 - Negara, Hasan Sastra; Angraini, Fitri (FONDATIA, 2024)
Rapid developments, especially in the era of Society 5.0, require adaptation in the education system to create a generation that is not only knowledgeable, but also has high creative and innovative skills. The purpose of this study is to describe the role of the independent curriculum in developing students' creative and innovative skills in the era of society 5.0. This study is included in the type of qualitative research with a descriptive method. The subjects of the study were teachers and students. Data collection through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model which includes data reduction, data display, and data verification. The results of the study show that (1) the independent curriculum that is implemented gives students more freedom to explore their interests and talents. (2) In determining students' interests and talents, teachers use diagnostic assessments in order to understand students' learning styles and interests because each student has a different way of learning. (3) The Independent Curriculum used integrates Pancasila values in every learning activity, such as teachers implementing project-based learning to strengthen the profile of Pancasila students (P5) by giving assignments or projects individually or in groups through coloring pictures, drawing Indonesian batik, and making ecoprint crafts . (4) Teachers apply various models to develop creative and innovative thinking skills in grade 4 elementary school students, one of which is through project-based learning. The conclusion of this study is that SD Islam Assalam Bandar Lampung has implemented an independent curriculum whose learning has developed student creativity and innovation through the project-based learning model and integrated Pancasila values in implementing P5-based learning.